Burden of injury in childhood and adolescence in 8 European countries - Polinder, Suzanne (BioMed Central, 2010)
BACKGROUND: Injury is the major cause of death and suffering among children and adolescents, but awareness of the problem and political commitment for preventive actions remain unacceptably low. We have assessed variation in the burden of injuries in childhood and adolescence in eight European countries. METHODS: Hospital, emergency department, and mortality databases of injury patients aged 0-24 years were analyzed for Austria, Denmark, Ireland, Latvia, Netherlands, Norway, Slovenia and the United Kingdom (England, Wales). Years lost due to premature mortality (YLL), years lived with disability (YLD), and disability adjusted life years (DALYs) were calculated. RESULTS: Differences in the burden of injury in childhood and adolescence are large, with a fourfold gap between the safest countries (Netherlands and UK) in western-Europe and the relatively unsafe countries (Latvia and Slovenia) in the east. Variation between countries is attributable to high variation in premature mortality (YLL varied from 14-58 per 1000 persons) and disability (YLD varied from 3-10 per 1000 persons). Highest burden is observed among males ages 15-24. If childhood and adolescence injuries are reduced to the level of current best injury prevention practices, 6 DALYs per 1000 child years can be avoided. CONCLUSIONS: Injuries in childhood and adolescence cause a high disability and mortality burden in Europe. In all developmental stages large inequalities between west and east are observed. Potential benefits up to almost 1 million healthy child years gained across Europe are possible, if proven ways for prevention are more widely implemented. Our children deserve action now.